2017
DOI: 10.3390/w9060432
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Dam-Break Flood Analysis in Data-Scarce Regions: The Case Study of Chipembe Dam, Mozambique

Abstract: This paper presents the results of a modeling study of the hypothetical dam break of Chipembe dam in Mozambique. The modeling approach is based on the software Iber, a freely available dam break and two-dimensional finite volume shallow water model. The shuttle radar topography mission (SRTM) online digital elevation model (DEM) is used as main source of topographic data. Two different DEMs are considered as input for the hydraulic model: a DEM based on the original SRTM data and a hydrologically-conditioned D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 45 publications
0
40
0
Order By: Relevance
“…The method used by Alvarez et al (2017) was considered for the classification of flood hazard in high, medium and low categories. To be classified in the high category, the location must have a water depth higher than 1 m, a water velocity greater than 1 m s −1 or a product of the velocity and the water depth greater than 0.5 m s −2 .…”
Section: Flood Hazard Mapping Methodologymentioning
confidence: 99%
“…The method used by Alvarez et al (2017) was considered for the classification of flood hazard in high, medium and low categories. To be classified in the high category, the location must have a water depth higher than 1 m, a water velocity greater than 1 m s −1 or a product of the velocity and the water depth greater than 0.5 m s −2 .…”
Section: Flood Hazard Mapping Methodologymentioning
confidence: 99%
“…However, in the data-scarce environment of the study area which is commonplace in many parts of Africa, a 10 m resolution is among the best in the region, especially when compared to Shuttle Radar Topography Mission (SRTM) and Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) Global Digital Elevation Model (GDEM) provided by the US Geological Survey (USGS). The example of some recent work (Jacobs et al, 2016;Alvarez et al, 2017) showed that using medium-or low-resolution products remains a valuable intermediate step to advance the understanding of flood risk in data-scarce areas in Africa, provided that the results are interpreted in light of the uncertainties affecting the input data.…”
Section: Topographic and Geophysical Datamentioning
confidence: 99%
“…The method used by Alvarez et al (2017) was considered for the classification of flood intensity in high, medium and low categories. To be classified in the high category, the location must have a water depth higher than 1 m, a water velocity greater than 1 m s −1 or a product of the velocity and the water depth greater than 0.5 m 2 s −1 .…”
Section: Flood Intensity Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Souza (2016) also mentions the impact that different Manning coefficients applied in the flood valley can generate in the results in relation to the peak flow. On the other hand, Rocha (2015) and Alvarez et al (2017) affirm that topography may be the main influencing factor in floodplain prediction, among other hydraulic variables of interest. In this 3/17 sense many research studies have been developed that connect the use of topography estimated by orbital sensors and large scale hydrodynamic modeling, presenting good results (YAN et al, 2015;ALSDORF et al, 2005;SCHUMANN et al, 2010).…”
Section: Introductionmentioning
confidence: 99%